Aortic Aneurysm Mimicking Inferior ST-Elevation Myocardial Infarction: A Case Report - Ahmed Qasim Mohammed Alhatemi MBChB; Ezzat Mohammed Hussain Aziz FRCP; Amjed Hussein Alwan Al-Yaseen FIBMS; Hashim Talib Hashim MD; Zaid Haitham Abduljabbar FIBMS; Salwan Qahtan Sultan FIBMS; Tiba Khalid Abdulhussain B.S.cPh; Rand Abdulhussain MSc (SAGE Publishing, 2024)
Here, we report a rare case of a 22-year-old female presenting with recurrent chest pain mimicking inferior ST-elevation myocardial infarction (STEMI) but ultimately attributed to an aortic aneurysm. Despite facing initial challenges in diagnosis, such as normal troponin levels and temporary electrocardiogram (ECG) changes, advanced imaging showed a large mass in the chest pressing on the right coronary artery. Prompt multidisciplinary intervention, including surgical resection of the aneurysm, led to successful management and improved outcomes. This case highlights the importance of considering unusual etiologies in atypical presentations of myocardial infarction, necessitating comprehensive evaluation and collaboration among various specialties for optimal patient care.